Improving National Security Using GPS Tracking System Technology - Akinode, J. L. (Mediterranean Journal of Social Sciences, 2011)
The spate of insecurity in Nigeria has received global attention lately and thus a need for an improved GlobalPositioning System (GPS) based tracking system is required to meet quickly evolving security issues in Nigeria. GPS trackingtechnology is one of the most rapidly growing technologies around the world. This paper is an attempt to explore the securitybenefits embedded in the GPS tracking system in respect to the National Security dilemma and its deployment into NigeriaSecurity System. The paper delves into the architecture of a GPS tracking system, the mechanism of GPS system and theimportance of geofencing and its application in the security of National emoluments(e.g refineries, mast e.t.c), human lives,Cars, Government facilities e.t.c. This paper is a clarion call to the Nigeria Government to implement an holistic approachtowards the realisation of the optimum utilization of the NIGCOMSAT satellite especially in the area of security of lives andproperties. This paper call the attention of the federal govt to the need for the full implementation of NIGCOMSAT Nigeria toavert some of the cases of bombing that has characterised the political landscape.Hence,a full implementation of SatelliteTracking Technology is capable of averting some of the security problem in the Nation.